Indonesia’s Judicial Review Regime in Comparative Perspective - Theunis Roux (The Constitutional Court of the Republic of Indonesia, 2018)
This paper provides a comparative perspective on judicial review in Indonesia after the establishment of the Constitutional Court in 2003. It starts by retelling the well-known story of the